Initial Effectiveness Evaluation of the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders for Homeless Women. Issue 3 (May 2022) - Rodriguez-Moreno, Sara; Farchione, Todd J.; Roca, Pablo; Marín, Carolina; Guillén, Ana I.; Panadero, Sonia
The purpose of this study is to evaluate the effectiveness of the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders adapted for homeless women (UPHW). Eighty-one homeless women participated in this single-blinded quasi-experimental clinical trial, involving up to 12 sessions of group treatment, and 3-and 6-month follow-ups. The participants received either immediate treatment with the UPHW ( n  = 46) or delayed treatment, following a 12-week wait-list control period (WLC; n  = 35). Primary outcomes included depression and anxiety. Secondary measures comprised positive and negative affect, psychological well-being, health perception, and social support. The UPHW resulted in significant improvement on measures of anxiety, depression and negative affect. Improvements in anxiety and depression were maintained over a 3-month follow-up period, but not at 6-month. The reliability of the clinical changes showed significant differences between UPHW and WLC for depression. Moreover, the inter-session assessment in the UPHW group showed a linear trend reduction for depression and anxiety scores along the 12 sessions. The clinical implications on the UPHW in social settings are also discussed.